Web of things: readiness and applications from a business and consumer perspective. (24th March 2015) - Sedgeman, Peter; Zuo, Yanjun
Web of things (WoT) is attractive in business applications and has been studied in a variety of areas, but its widespread adoption has not yet come. In this paper we focus on the readiness and potential applications of WoT from a business and consumer perspective. We have identified some outstanding issues that affect WoT's wide application in business and consumer markets. We provide some use cases to illustrate the viable potential of applying WoT in different business fields and highlight the importance of solving those outstanding issues. Finally, we offer ideas for potential avenues to overcome some of the challenges presented and suggest guidelines that businesses should consider when contemplating WoT adoption.